Investigating the impact of digital textbooks on students’ digital literacy - Danil Darmawan; Bambang Ruby Sugiarto; Leni Irianti (Universitas Galuh, 2026)
The integration of digital textbooks in English as a Foreign Language (EFL) classroom has become more common, particularly as digital literacy grows in importance for 21st-century learners. While many digital learning tools are available, there is limited research that closely examines how digital textbooks contribute to students’ digital literacy development in real classroom practice, especially in EFL contexts. This study aimed to explore how the use of digital textbooks contributes to students’ digital literacy development in EFL learning from both student and teacher perspectives. A qualitative case study was conducted involving classroom observations and semi-structured interviews with students and an English teacher. The analysis was guided by Hague and Payton’s digital literacy framework by covering eight aspects: functional skills, creativity, critical thinking and evaluation, cultural and social understanding, collaboration, ability to find and select information, effective communication, and safeguarding. The findings indicated that digital textbooks supported several aspects of digital literacy, particularly functional skills, information selection, and critical evaluation. However, certain aspects, such as creativity and safeguarding, were less frequently observed. The study concludes that digital textbooks have the potential to foster digital literacy in EFL settings, but their effectiveness depends on how actively features are utilized and supported through guided classroom practices.